Effect of Precursor Concentration on Structural and Optical Properties of MoO3 Thin Films Deposited by Spray Pyrolysis - P. Shanthini Grace (Revista Electronica de Veterinaria, 2024)
Molybdenum trioxide (MoO3) thin films were deposited on glass substrates via microprocessor-controlled spray pyrolysis using precursor concentrations of 0.01 M, 0.03 M, and 0.05 M at 200°C. Structural analysis using X-ray diffraction (XRD) revealed amorphous nature at 0.01 M, transitioning to polycrystalline orthorhombic phase (JCPDS 05-0506) at higher concentrations, with lattice parameters a ≈ 3.94 Å, b ≈ 13.86 Å, c ≈ 3.69 Å. Crystallite size increased from ~15 nm to 16 nm, while microstrain (×10⁻⁴) and dislocation density (×10¹⁴ lines/m²) decreased with concentration. Optical studies (UV-Vis, 300-900 nm) showed transmittance reduction and direct band gap narrowing from 3.6 eV (0.01 M) to 3.4 eV (0.05 M), attributed to enhanced crystallinity. These findings highlight concentration as a key parameter for tailoring MoO3 films for electrochromic, sensor, and solar applications.